Bimodal Release Ondansetron Improves Stool Consistency and Symptomatology in Diarrhea-Predominant Irritable Bowel Syndrome: A Randomized, Double-Blind, Trial. (24th September 2020) - Plasse, Terry F.; Barton, Gary; Davidson, Evelyne; Abramson, Danielle; Kalfus, Ira; Fathi, Reza; Raday, Gilead; Harris, M. Scott
Abstract : INTRODUCTION: Previous, small studies have suggested that ondansetron has beneficial effects in diarrhea-predominant irritable bowel syndrome (IBS-D). This randomized, double-blind study evaluated the efficacy and safety of daily 12 mg RHB-102, an investigational bimodal release ondansetron tablet, in IBS-D. METHODS: Men and women with IBS-D by the Rome III criteria, Bristol Stool Scale ≥6 on 2 or more days weekly, and average daily worst pain intensity ≥3/10 were randomized 60:40 to RHB-102 or placebo once daily for 8 weeks. The primary end point was overall stool consistency response for at least 4 of 8 weeks. Secondary end points included overall worst abdominal pain and overall composite response, defined as response on both abdominal pain and stool consistency end points. RESULTS: Overall stool consistency response rates were 56.0% and 35.3% (RHB-102 vs placebo, P = 0.036) and similar among male and female patients. Overall pain response (50.7% vs 39.2%) and composite response rates (40.0% vs 25.5%) favored RHB-102, although these differences were not statistically significant. Stool consistency response rates were enhanced in patients with baseline C-reactive protein above the median (2.09 mg/L), 59.5%, vs 23.1% ( P = 0.009). Overall rates of adverse events were similar, with a higher rate of constipation in RHB-102 patients (13.3% vs 3.9%) that resolved rapidly on withholding treatment. DISCUSSION: RHB-102 was effective and safe in the treatment of men and women with IBS-D. Baseline C-reactive protein seemed to be predictive of response.